Exploring Workplace Learning in University Education Through a 'Slow Innovations' Framework : Curation, Innovation and Exemplary Practice : Final Report. - Simpson, Maree Donna; Gates, Alison (Office for Learning and Teaching, 2014)
This report looks at workplace learning in university education and how it can work and a framework for it. Workplaces as authentic sites of practice can foster the development of capabilities and professional identity among students across diverse areas of study, but it is not without its challenges. The issue the authors wished to address was the increased pressure to rapidly expand workplace learning initiatives in Australian higher education amidst a complex environment. How workplace learning can be more mindfully shaped so as to create positive repercussions for all stakeholders is relatively underexplored. The findings of this study will be of value to a broad range of stakeholders, including: educators, administrative staff, university managers and workplace learning partners. What will be valuable is the increased awareness and understanding this study will present in terms of: which workplace learning innovations are successful, why they are successful and for whom they are successful. Identifying the innovations and implications within this workplace learning ecology of interrelationships aims to inform and enhance the shaping and sustainability of future work-integrated learning.